1991
DOI: 10.1152/ajprenal.1991.260.6.f913
|View full text |Cite
|
Sign up to set email alerts
|

Localization of endothelin-like immunoreactivity in rat kidneys

Abstract: The distribution of endothelin-like immunoreactivity was examined in normal rat kidneys using the immunoperoxidase technique. A specific polyclonal antibody to endothelin 1, which recognized endothelin 1 and its precursor molecule, big endothelin, was raised in rabbits. Immunoperoxidase staining revealed specific endothelin-like immunoreactivity in the renal cortex, medulla, and papilla. Immunostaining density was greatest in the renal papilla where staining was predominantly localized to the vasa rectae of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…In situ hybridization of renal cortex revealed no ET-1 mRNA in any mice (floxed ET-1, AQP2-Cre, or CD ET-1 KO). The lack of detectable renal cortical ET-1 is in agreement with other studies using in situ hybridization, immunostaining, or RT-PCR of immunodissected CCD (6,8,38,39). To confirm that recombination had occurred in CCDs, the ducts were microdissected and DNA PCR amplified using the primers used for genotyping.…”
Section: Resultssupporting
confidence: 88%
“…In situ hybridization of renal cortex revealed no ET-1 mRNA in any mice (floxed ET-1, AQP2-Cre, or CD ET-1 KO). The lack of detectable renal cortical ET-1 is in agreement with other studies using in situ hybridization, immunostaining, or RT-PCR of immunodissected CCD (6,8,38,39). To confirm that recombination had occurred in CCDs, the ducts were microdissected and DNA PCR amplified using the primers used for genotyping.…”
Section: Resultssupporting
confidence: 88%
“…The latter is separated from distal tubules in vivo by only a very narrow interstitial space (45), permitting paracrine or autocrine communication among cell types. In addition, microdissected cortical collecting tubules contain ET-1 mRNA (43,46), and ET-1 is on the endothelial surfaces of peritubular capillaries (44). The present studies show that dietary acid increases RIF ET-1 addition and suggest that the added ET-1 subsequently increases distal tubule acidification.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, rat cortical collecting tubules contain mRNA for the B-type endothelin receptor (43), which the present studies suggest mediates the described actions of endogenous endothelins. Endothelins in the RIF might derive from collecting tubule epithelium (5) or endothelium of the renal microvasculature (6,44). The latter is separated from distal tubules in vivo by only a very narrow interstitial space (45), permitting paracrine or autocrine communication among cell types.…”
Section: Discussionmentioning
confidence: 99%
“…13 - 15 In addition, receptors for both peptides have been identified in the glomeruli, vasa recta, and medulla. 22 Localized stimulation of renal Ang II formation by ET-1 therefore could contribute to the observed hypertension, which would be reversed by an action of captopril on renal ACE. In support, one recent investigation performed in anesthetized dogs and rats demonstrated that captopril attenuated ET-1-induced decreases in renal blood flow, urinary sodium excretion, and urine flow, while having little effect on the shortterm pressor response to ET-1.…”
Section: C1 C2 C3 E1 E2 E3 E4 Es E« E7 R1 R2 Rj R4 R5mentioning
confidence: 99%